2004
DOI: 10.1093/ajcn/80.3.584
|View full text |Cite
|
Sign up to set email alerts
|

Associations between objectively assessed physical activity and indicators of body fatness in 9- to 10-y-old European children: a population-based study from 4 distinct regions in Europe (the European Youth Heart Study)

Abstract: The accumulated amount of time spent at moderate and vigorous PA is related to body fatness in children, but this relation is weak; the explained variance was <1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
273
3
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(312 citation statements)
references
References 38 publications
22
273
3
14
Order By: Relevance
“…It should also be acknowledged that there is poor to moderate agreement between accelerometry and energy expenditure, and that the Actigraph has poor validity against indirect calorimetry and double-labelled water, especially in young Physical activity and body composition D Moliner-Urdiales et al children, 45 whereas less evidence exist for adolescents. It should be mentioned that the cutoff points used in this study to define physical activity intensities are similar to those used in previous studies, 16,31,32 and that seem to be useful and valid for estimating participation in moderate and vigorous physical activity in children and adolescents, particularly time spent in vigorous physical activity. 46,47 Furthermore, it seems that among the commercially available accelerometers, the one used in this study (Actigraph MTI, model GT1M) showed the best correlation with doubly labelled water derived energy expenditure.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…It should also be acknowledged that there is poor to moderate agreement between accelerometry and energy expenditure, and that the Actigraph has poor validity against indirect calorimetry and double-labelled water, especially in young Physical activity and body composition D Moliner-Urdiales et al children, 45 whereas less evidence exist for adolescents. It should be mentioned that the cutoff points used in this study to define physical activity intensities are similar to those used in previous studies, 16,31,32 and that seem to be useful and valid for estimating participation in moderate and vigorous physical activity in children and adolescents, particularly time spent in vigorous physical activity. 46,47 Furthermore, it seems that among the commercially available accelerometers, the one used in this study (Actigraph MTI, model GT1M) showed the best correlation with doubly labelled water derived energy expenditure.…”
Section: Discussionsupporting
confidence: 53%
“…The inverse relationship between objectively assessed PA and body fat agree with previous studies. [1][2][3][4][5][6][7][8][9][10][11] Lohman et al 6 reported a significant association of total body fat assessed by anthropometry with MVPA and vigorous PA. Wittmeier et al 3 investigated 251 Canadian children aged 8-11 years and observed that time spent in MVPA was inversely correlated with body mass index and a skinfold-derived Abbreviations: MVPA, moderate and vigorous physical activity; PA, physical activity. All variables were log transformed, except light and moderate PA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, earlier studies have been inconsistent in adjusting for dietary behaviors known to affect childhood overweight, such as consumption of breakfast and sugar-sweetened beverages [12-14,16]. Therefore, confounding by these factors cannot be ruled out.…”
Section: Introductionmentioning
confidence: 99%